Analyses of human immune responses to Francisella tularensis identify correlates of protection - Lindgren, Helena; Eneslätt, Kjell; Golovliov, Igor; Gelhaus, Carl; Sjöstedt, Anders (Frontiers in Immunology, 2023)
Francisella tularensis is the etiological agent of the potentially severe infection tularemia. An existing F: tularensis vaccine, the live vaccine strain (LVS), has been used to protect at-risk personnel, but it is not licensed in any country and it has limited efficacy. Therefore, there is a need of a new, efficacious vaccine. The aim of the study was to perform a detailed analysis of the characteristics of the human immune response to F. tularensis, since this will generate crucial knowledge required to develop new vaccine candidates. Nine individuals were administered the LVS vaccine and peripheral blood mononuclear cells (PBMC) were collected before and at four time points up to one year after vaccination. The properties of the PBMC were characterized by flow cytometry analysis of surface markers and intracellular cytokine staining. In addition, the cytokine content of supernatants from F. tularensis-infected PBMC cultures was determined and the protective properties of the supernatants investigated by adding them to cultures with infected monocyte-derived macrophages (MDM). Unlike before vaccination, PBMC collected at all four time points after vaccination demonstrated F. tularensis-specific cell proliferation, cytokine secretion and cytokine-expressing memory cells. A majority of 17 cytokines were secreted at higher levels by PBMC collected at all time points after vaccination than before vaccination. A discriminative analysis based on IFN-γ and IL-13 secretion correctly classified samples obtained before and after vaccination. Increased expression of IFN-γ, IL-2, and MIP-1β were observed at all time points after vaccination vs. before vaccination and the most significant changes occurred among the CD4 transient memory, CD8 effector memory, and CD8 transient memory T-cell populations. Growth restriction of the highly virulent F. tularensis strain SCHU S4 in MDM was conferred by supernatants and protection correlated to levels of IFN-γ, IL-2, TNF, and IL-17. The findings demonstrate that F. tularensis vaccination induces long-term T-cell reactivity, including TEM and TTM cell populations. Individual cytokine levels correlated with the degree of protection conferred by the supernatants. Identification of such memory T cells and effector mechanisms provide an improved understanding of the protective mechanisms against F. tularensis. mechanisms against F. tularensis.